The Effect Of Aerosolised-Honey On Inflammation, Regeneration And Repair Of Airway Epithelia In Rabbit Model Of Ovalbumin-Induced Chronic Lung Injury - Kamaruzaman, Nurfatin Asyikhin (2017)
For the past few decades, chronic lung injury has attributed to thousands of death worldwide. The disease occurred due to alteration in the structure as well as cellular components of the airways which later lead to airway remodelling and inflammation. This disease is not curable; however, treatments are available to reduce the disease symptoms and preventing the disease progression. At the clinical setting, conventional drug therapy is available to lessen disease exacerbations; however, there is still a need to find the alternative treatments that incorporated with natural resources to minimize the side effect of drug therapy.